Informed participation: The effects of information treatment on panel non-response - Ricardo Santos; Sam Jones (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper builds on a longitudinal school-to-work transition phone survey experiment to quantify the effects on attrition of communicating with participants. Specifically, we study the impact of sending topically relevant information on job market conditions via SMS at the start of each survey round. Testing various information treatments, which differ in their granularity, including survival analysis, we find they all significantly reduce the instantaneous risk of nonresponse, with an estimate of instantaneous hazard reduction of around 30 per cent. These results affirm the best-practice recommendation to establish communication with participants between survey rounds to continue survey participation.
Keywords: C41; C83; J20; J63; 330; survey participation; attrition; information; survival analysis